Burkina Faso : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Requests for Waiver of Nonobservance of Performance Criterion, and Deletion of Performance Criteria; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burkina Faso. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper discusses key findings of the Second Review Under the Poverty Reduction and Growth Facility for Burkina Faso. All quantitative performance criteria (PC) were met. The indicative floor on social expenditures was not achieved, mainly because of capacity weaknesses in implementing capital expenditures. The implementation of the tax and customs administration agenda was broadly in line with the program. IMF staff supports the authorities' request for a waiver for the nonobservance of a continuous structural PC on sending notification letters within one week to late and nonfilers of tax returns.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet